A Review of the Book The Art of Islamic Banking and Finance - S.M.Reza Amiri Tehrani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The Art of Islamic Banking and Finance narrates the author’s (Yahia Abdul- Rahman) achievement in ‎constituting an interest-free bank in the U.S.A. As a matter ‎of fact, he explores banking and finance laws ‎and regularities in the U.S as well as the Islamic banking ‎system in the world. The remarkable difference between ‎these two kinds of banking systems is that the ‎former is based on the monetary market and the latter on ‎the real economy. In the Islamic banking system, ‎the rent expense of a commodity to be financed is ‎measured based on rules known as “commodity ‎indexation” and “marking to market”. Moreover, in ‎such a system, the interest rate of the ordinary ‎banking system is substituted with the rent expense of ‎a commodity. Thus, rent expenses are not ‎fixed like interest rates. The prominent characteristic of an ‎Islamic banking system is not only its ‎interest-free feature but also its civility and social responsibility. The main pitfalls of the book include a lack of comprehensive discussion and a lack of reporting the Islamic banking systems of other Muslim countries. Besides, no thorough analysis of banking system experiences has been done and has not paid attention to the critique of the Iranian banking system.